Gender Categorization in Cochlear Implant Users. - Massida, Zoé; Marx, Mathieu; Belin, Pascal; James, Christopher; Fraysse, Bernard; Barone, Pascal; Deguine, Olivier (Journal of Speech, Language & Hearing Research, 2013)
Purpose: In this study, the authors examined the ability of subjects with cochlear implants (CIs) to discriminate voice gender and how this ability evolved as a function of CI experience. Method: The authors presented a continuum of voice samples created by voice morphing, with 9 intermediate acoustic parameter steps between a typical male and a typical female. This method allowed for the evaluation of gender categorization not only when acoustical features were specific to gender but also for more ambiguous cases, when fundamental frequency or formant distribution were located between typical values. Results: Results showed a global, though variable, deficit for voice gender categorization in CI recipients compared with subjects with normal hearing. This deficit was stronger for ambiguous stimuli in the voice continuum: Average performance scores for CI users were 58%lower than average scores for subjects with normal hearing in cases of ambiguous stimuli and 19% lower for typical male and female voices. The authors found no significant improvement in voice gender categorization with CI experience. Conclusions: These results emphasize the dissociation between recovery of speech recognition and voice feature perception after cochlear implantation. This large and durable deficit may be related to spectral and temporal degradation induced by CI sound coding, or it may be related to central voice processing deficits.